Multi-Hop Selective Constructive Interference Flooding Protocol For Wireless Sensor Networks - Alhalabi, Huda A. H. (2019)
Connectivity is a critical issue in WSNs, as the data collected needs to be sent to the base station or the processing centers. Low connectivity due to the limited radio range of sensor nodes and random distribution leads the network to be partitioned into disconnected groups, which can interrupt or completely prevent communication between nodes. For effective communication, each node must be located close enough to each other. Improper positioning of the nodes can cause a failure in sending or receiving radio signals, resulting in a segmented or incomplete network. A Multi-Hop Selective Constructive Interference Flooding (MSCIF) protocol is proposed to address the problem of low connectivity in WSNs with a sparse distribution and improve the network’s lifetime. MSCIF integrates three main algorithms: clustering algorithm, selection algorithm, and a synchronized flooding. The first step of the proposed protocol involves the development of an energy efficient clustering algorithm which is appropriate for WSN with a sparse density topology. Clustering is necessary in the proposed protocol as it helps to exclude nodes that are far away from other nodes, which consume a lot of energy. The stages of clustering are: initialization, scheduling, and clustering. The second step in MSCIF protocol involves designing a selection algorithm to select the minimum connected dominating nodes. This is to improve the network reliability and control the energy consumption by reducing the number of cooperating nodes. The third step is applying a fast-synchronized flooding to achieve a constructive interference at the receiver to improve the received signal strength and improve connectivity.